2009
DOI: 10.1002/pssb.200880506
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence in quantum well heterostructures p‐AlxGa1–xAs/GaAs1–yPy/n‐AlxGa1–xAs under uniaxial stress

Abstract: This article summarizes some of the key findings of a report (HM Inspectorate of Probation, 1998) of an inspection of the work of the probation service in England and Wales with sex offenders. The inspection took place at a time of unprecedented public debate and concern about the nature and impact of sexual offending, but this focused attention on a few high‐profile individuals rather than the majority of sexual offenders who assaulted victims that were known to them. For the purposes of the inspection, 10 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Tomm et al [20] have shown experimentally that such pristine devices are essentially uniaxially compressed along the [110] direction; the initial average device compression in the center of the laser bar was determined to about −0.16% for a standard indium soldering process on a copper heat sink, whereas the packaging-induced strain for AuSn mounting on CuW is smaller by one order of magnitude [21]. We have observed a blue shift of the EL spectrum by about 25 meV under uniaxial compression of P=5 kbar on our samples with 0.55 mm cavity [3] that corresponds to a reduction of the in-built tensile strain by about −0.19%. This reduction was calculated as described in [4,15] and is confirmed by the agreement between the calculated change of the optical gap and the observed blue shift of the EL spectrum under uniaxial compression [4].…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Tomm et al [20] have shown experimentally that such pristine devices are essentially uniaxially compressed along the [110] direction; the initial average device compression in the center of the laser bar was determined to about −0.16% for a standard indium soldering process on a copper heat sink, whereas the packaging-induced strain for AuSn mounting on CuW is smaller by one order of magnitude [21]. We have observed a blue shift of the EL spectrum by about 25 meV under uniaxial compression of P=5 kbar on our samples with 0.55 mm cavity [3] that corresponds to a reduction of the in-built tensile strain by about −0.19%. This reduction was calculated as described in [4,15] and is confirmed by the agreement between the calculated change of the optical gap and the observed blue shift of the EL spectrum under uniaxial compression [4].…”
Section: Resultsmentioning
confidence: 70%
“…The compressive or tensile strained III-V layered heterostructures with quantum wells (QW), which are the main functional materials for semiconductor laser diodes and other optoelectronic devices, offer unprecedented flexibility for band structure engineering [1]. They are highly sensitive to external hydrostatic [2] and uniaxial [3] compression. Under [110] uniaxial compression (P≈5 kbar), the electroluminescence (EL) spectrum in p-Al 0.45 Ga 0.55 As/ GaAs 0.84 P 0.16 /n-Al 0.45 Ga 0.55 As laser diodes demonstrates a blue shift up to 25 meV [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, metal-insulator transitions were investigated under uniform pressure in bulk 1 and low-dimensional 2 materials, and a range of electronic topological transitions under uniaxial compression were detected. 3 Recently, the possibility of laser diodes wavelength tuning by means of uniaxial stress 4 and uniform compression in hydrostatic pressure cells 5 has been successfully demonstrated.…”
Section: Introductionmentioning
confidence: 99%